Intravenous Dihydroergotamine Therapy for Pediatric Abdominal Migraines. (October 2013) - Raina, Madiha; Chelimsky, Gisela; Chelimsky, Thomas
Abdominal migraines present with debilitating symptoms in adolescence. At our institution, the gastroenterology, neurology, and autonomic departments collaborated in treating patients with such presentations. This case series describes 6 patients who were given intravenous dihydroergotamine (DHE) for presumed abdominal migraines. DHE was only used when other agents like amitriptyline, verapamil, topiramate, or depakote had proved ineffective. DHE was started at 0.5 mg dose and on average 7 to 9 mg were given on each hospitalization. Patient ages ranged from 13 to 19 years with the majority being female. One patient did not respond to treatment. One patient was admitted 4 times for symptoms of abdominal migraines resolving with DHE. The average time between symptom relapse was about 5 to 12 months. Five of our 6 patients responded to the infusion without significant side effects. Based on these case series, DHE may be a treatment option in children with intractable abdominal migraine.